Reliability and Cost Model of P.M. in A Component of an Electrical Distribution System Considering Ageing Mechanism - Saeed Afshar; M Fotuhi Firuzabad (Institute of Advanced Engineering and Science, 2014)
Application of Reliability Centered Maintenance (RCM) in a system results in a decrease in component failure rates and as such improvement in the system reliability. One of the major subjects of the RCM is focused on the Online and Offline Preventive Maintenance (OPM and FPM which together will be denoted by OFPM) of the components which repairing the component needs or doesn’t need to stop the mission carrying out by it. The RCM is classified as a preventive maintenance policy and has significant contribution in practical applications. However, little research has been devoted to modeling the online and offline Preventive Maintenance. This research assumes that the component failure rate will be improved if the OFPM is performed for a long period of time as a part of an RCM program. Application of an OFPM program could cause the component set at least to “as bad as old state but cannot reach the “as good as new” state. The emphasis of this research is to model the OFPM for critical components or any equipment with critical failure in a system. The proposed model is based on the concept of PM and improvement factor of reliability in a system with critical components which their failure could cause a failure in the system (first-order cut- sets).DOI:http://dx.doi.org/10.11591/ijece.v4i2.5514